Alarm Fatigue among Nurses Working in Critical Care Setting in a Tertiary Hospital, Nepal - Regmi, B; Shrestha, B; Khanal, S; Moktan, S; Byanju, R (Kathmandu University Medical Journal, 2023)
Background Alarm fatigue is a well-recognized patient safety concern in critical care settings. It occurs when nurses become overwhelmed by the total number of alarm signals which can result in alarm desensitization and eventually contributes to missing of serious and important changes in a patient’s condition, thus failing to respond properly. Objective To find out alarm fatigue and its associated factors among nurses working in critical care setting. Method A cross-sectional study design with convenient sampling technique was used to select 56 nurses working at different critical care settings in Dhulikhel Hospital. A self-constructed semi structured questionnaire and nurses alarm fatigue questionnaire was used for the survey. Frequency, percentage, mean and standard deviation were used for descriptive statistics whereas Independent t-test and One-way ANOVA were used for inferential statistics. Result The result shows that more than half of the nurses were less than 25 years, single and more than two-third of the participants worked in Adult Intensive Care Unit. Out of total obtainable score 44, the overall mean score of the Alarm Fatigue was 28.03±12.813. The result showed that there was no significant difference between alarm fatigue and selected socio-demographic and work related characteristics. Conclusion The alarm fatigue among nurses working in critical care settings was found to be higher in this study. Since alarm fatigue is directly related to patients’ safety, the effective management of medical device alarms can reduce alarm fatigue and prevent potentially dangerous outcomes.